Profitability, Ownership, Risk, and Deposit Insurance of Commercial Banks in Africa - (:unkn) unknown (My University, 2025)
The paper empirically examines the relationship between profitability, ownership structure, bank risk (Z-score), and deposit insurance schemes in African commercial banks. Using the Generalized Method of Moments (GMM) and Fixed Effects (FE) estimation techniques with sample data of 141 banks in 19 African countries from 2009-2020.The study presents four key findings, first, foreign ownership decreases bank return on equity (ROE), while state ownership enhances it. Second, a higher Z-score enhances bank stability, reduces risk, and increase profitability. Third, Deposit insurance negatively impacts profitability and increases risk in the short term. However, explicit deposit insurance could enhance profitability by 0.6% in the long run. Finally, bank capitalization, size, asset composition, and macroeconomic factors (GDP, inflation) are critical determinants of profitability in Africa. Policymakers should consider these factors when designing policies to enhance banking sector stability and growth, including the adoption and implementation of explicit deposit insurance in Africa.
Keywords: African Research